2020
DOI: 10.4103/jcd.jcd_345_19
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the fracture resistance of endodontically treated teeth with simulated invasive cervical resorption cavities restored with different adhesive restorative materials: An in vitro study

Abstract: Aim: The aim of the study was to compare the fracture resistance of endodontically treated teeth with simulated invasive cervical resorption cavities, restored with different restorative materials, namely, conventional glass-ionomer cement (CGIC), resin-modified glass-ionomer cement (RMGIC), flowable composite (FC), and giomer. Methods: Sixty extracted human permanent maxillary central incisor teeth were assigned to six groups,which were, Group 1 (intact teeth, control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…To overcome this potential problem, we calculated the mean fracture resistance of several samples for each group. Since ECR defects are often diagnosed at a more advanced stage due to their asymptomatic nature ( 8 ), endodontic therapy is often part of the treatment plan, leading to the decision to perform root canal treatment on all specimens in the study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To overcome this potential problem, we calculated the mean fracture resistance of several samples for each group. Since ECR defects are often diagnosed at a more advanced stage due to their asymptomatic nature ( 8 ), endodontic therapy is often part of the treatment plan, leading to the decision to perform root canal treatment on all specimens in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar in-vitro study ( 8 ), the authors compared the fracture resistance to oblique loading on simulated ECR defects in maxillary central incisors restored with Giomer, RMGIC, conventional GIC and flowable resin composite. Although they concluded that Giomer showed significantly better results compared to the other materials, a major limitation of the study was the absence of periodontal ligament simulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations